Keefektifan CTL Berbantuan Ular Tangga dalam Meningkatkan Kemampuan Berpikir Kritis dan Pemecahan Masalah Matematika Siswa - Laela Musri Kholifah; Nursiwi Nugraheni (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
The primary objective of this investigation was to evaluate how effectively the Contextual Teaching and Learning (CTL) model, when integrated with a Snakes and Ladders board game, enhances the critical thinking and problem-solving capabilities in mathematics. This research employs a quasi-experimental design. The analysis revealed that the proportion of students achieving mastery in the experimental group exceeded 75%. Furthermore, the independent t-test confirmed a significant performance gap between the treated and untreated groups, as evidenced by a Sig. (2-tailed) value of 0.000 < 0.05. Additionally, the internal group evaluations via paired t-tests also demonstrated a significant improvement in scores from the initial assessment to the final assessment. The experimental class’s N-Gain was in the high range at 0.7043 and 0.7103, whereas the control class’s improvement was in the moderate range at 0.5200 and 0.5441. Based on these research results, the CTL model, aided by the snakes and ladders game, is effective in enhancing critical thinking and mathematical problem-solving capabilities among fourth-grade students at SDN Putatsari regarding the topic of area and volume measurement.